Konsep Lera-Wulan Tana-Ekan Orang Lembata dalam Tinjauan Filsafat Agama Hegel: Suatu Upaya Berdialog - Tatap, Eric Yohanis (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2022)
Faith and culture are often considered as interesting areas of topics for the academic discussions. They can become fruitful dialogue partners in the search of truth. Each area refers to the sources of truth at different levels compared to others outside of their areas. This article is an effort to reconcile the truth claims on the ontological and empirical levels by way of dialogue. The dialogue raised here brings together religion in Hegel’s philosophy and the cultural belief of the Lembata people called Lera-Wulan Tana-Ekan. Both are on different paths, one is a series of philosophical ideas while the other is a local wisdom from a certain part of Indonesia, particularly among the Lembata people in East Nusa Tenggara. This article aims to elevate the claims of truth that exist in a belief from a certain culture to the public domain of philosophy. The method used in this writing is dialectical by analyzing whether the ideas in Hegel’s philosophy of religion are in line with the beliefs held by the Lembata people. The belief in the universe, the highest morality, and the origin of creation are analyzed in relation to the movement of the Spirit discussed by Hegel in the natural religion, the religion of art, and the revealed religion.